Microsoft office excel 2003: - Hagg, Stephen (McGraw-Hill, 2004)
The I-Series Applications textbooks strongly emphasize that students learn and master applications skills by being actively engaged- by doing. These texts have been written with clear, error-free, and unambiguous steps to accomplish tasks that lead to a finished document, worksheet or database table. The authors made the decision that teaching how to accomplish some task is not enough for complete understanding and mastery. Prior to introducing steps, the authors discuss why the steps students are about to experience are important and what role the steps play in the overall plan for creating a document, workbook or database.